Critical behavior near the paramagnetic-ferromagnetic phase transition in polycrystalline La0.6Ca0.2Ba0.15□0.05MnO3. Issue 11 (15th August 2016) - Sfifir, I.; Nasser, N. Ouled; Khlifa, H. Ben; Cheikhrouhou-Koubaa, W.; Koubaa, M.; Cheikhrouhou, A.
Abstract: In this paper, we present a detailed study on the structural and critical behavior around paramagnetic (PM)-ferromagnetic (FM) phase transition in La0.6 Ca0.2 Ba0.15 □0.05 MnO3 (LCBMO). Our powder specimen was synthesized using the conventional solid-state reaction method and was analyzed by X-ray diffraction and magnetic measurements. X-ray diffraction analysis, at room temperature, shows that LCBMO adopts an orthorhombic structure with Pbnm space group. Detailed analyses of magnetic-field dependences of magnetization in the vicinity of the paramagnetic-ferromagnetic transition, M(H, T), reveal that LCBMO undergoes a second-order magnetic phase transition. Critical behavior has been studied through various techniques such as modified Arrott plot (MAP), Kouvel-Fisher method (KF) and critical isotherm (CI) analysis. The estimated Critical exponents are close to those expected for the mean-field model (β=0.5, γ=1 and δ=3). The reliability of the critical exponent values was confirmed by the Widom scaling relation, as well as the universal scaling hypothesis.